Mackenzie pipeline hearings, Hyatt Regency - Pacific Tribune (photographer) (1976)
Hearings conducted by the Berger Inquiry into the Mackenzie Valley Pipeline opened in Vancouver May 10, 11 and 12 before moving to Calgary.